Neonatal Resuscitation Preparedness Among Healthcare Provider: A Systematic Review - Ika Rizki Anggraini; Kuswantoro Rusca Putra; Setyoadi (GoAcademica Research & Publishing, 2020)
Neonatal asphyxia is a form of gravity that occurs in neonates. It is a condition when the baby cannot breathe spontaneously and regularly after birth. The management of neonatal resuscitation is carried out by the health team. It is provided by nurses, midwives, and physicians. To identify the evidence of health team readiness in administering neonatal emergencies is useful to succeed neonatal resuscitation. The selection was conducted by following PRISMA flow diagram. It was also criticized by JBI tool. The search keywords were “Readiness Factor” and “Neonatal Resuscitation”. The steps consisted of making questions, identifying, eligibility, article inclusion selection, screening, and appraisal. After 11 relevant articles were collected, they were analyzed in a systematic review. The finding shows that readiness in carrying out neonatal resuscitation requires preparation from both the health team that administers these actions. It consists of six dimensions. These dimensions are knowledge, clinical skills, self-efficacy, handling algorithms, facilities, and medicine. They are interrelated with one another towards a successful neonatal resuscitation.